An Archaeological Examination of the Material from the Syrian Sites of the Second Millennium 1800-1300 B.C. Ph. D. Vol. II (Plates) - Seton Williams, Marjory Veronica (2000)
Typescript; 1. The geographical background and routes; 2. The sites; 3. The economic development of Syria in the 2nd millennium B.C.; 4. Population and fauna; 5. The metals; 6. The architecture; 7. Tombs and graves; 8. Pottery; 9. Metal weapons, tools and utensils; 10. Art and small antiquities; 11. Texts. App. Ancient place names – Classification of metal objects.